Roller skiing biomechanical information analysis using GPS, IMU, and atmospheric pressure sensors: a case study - Moon, J.; Kim, J.; Kim, J.; Kim, J.; Kim, C.; Kim, H. (Sports Engineering, 2018)
The purpose of this research was to propose a method to acquire the three-dimensional movement of a roller skiing athlete utilizing a global positioning system (GPS), an atmospheric pressure sensor (APS), and an inertial measurement unit (IMU) to distinguish between diagonal skiing and double poling techniques. In this study, we developed a lightweight wearable sensor that was composed of a GPS, APS, and IMU. For the data collection, two national level athletes roller skied a 1700 m long course where the maximum difference in elevation was 5.3 m. The planar positions of the athletes were based on the longitudinal and latitudinal data provided by the GPS, and the altitude was calculated by the International barometric formula and Laplace transform from the APS. The longitudinal and latitudinal data acquired through GPS had errors within 2 m range at each point. The altitude of Laplace transform from the APS showed errors of less than 1 m at each point. The range of motion of pelvis from the IMU was 34.0 ± 3.8° for diagonal skiing, which is wider than the 21.2 ± 6.9° for double poling.